PROTOPLAST FUSION BETWEEN WHITE AND BROWN OYSTER MUSHROOMS - Djajanegara, Ira; Masduki, Agus (Indonesian Agency for Agricultural Research and Development - MOA, 2010)
Genetic crossing of white oyster mushroom (Pleurotus floridae)to introduce longer storage life trait can only be done withinindividuals in this particular species. However, longer storagelife trait is possessed by brown oyster mushroom (Pleurotuscystidiosus). Therefore, a protoplast fusion experiment betweenwhite and brown oyster mushrooms was conducted to obtain anoyster mushroom strain showing high productivity and longstorage life. The experiment was done at the biology laboratoryof the University of Al Azhar Indonesia from May 2008 toAugust 2009. Protoplast fusion was done by isolating protoplastfrom 5-day old monokaryotic mycelia grown in potato dextrosebroth (PDB). Around 3.15 x 105 protoplasts ml-1 were harvestedusing mixture of cellulase Onozuka R-10 (1%) and macerozymeR-10 (1%) from brown oyster mushroom with 80.61% viability.Similarly, 3.71 x 105 protoplasts ml-1 were harvested using lysingenzyme (2%) from white oyster mushroom with 83.68% viability.Protoplast fusions were conducted using 40% PEG6000 for10 minutes. The candidate fusants were then screened usingminimum regeneration media (MRM). There were 22 coloniesgrew on MRM media and four colonies (FS1, FS2, FS3, and FS4)showed clamp connection as well as primordia formation to bechosen as candidate fusants. However, isozyme studies usingmalate dehydrogenase and acid phosphatase as marker enzymesconfirmed that only FS1 and FS2 were the hybridized products.The two colonies showed different mycelia growth patterns andhyphae sizes, fruit body morphology and productivity comparedto their parents. These two fusants, however, did not indicatethe presence of longer storage life trait as expected despite ahigher productivity achieved by FS1. In this study, the protoplastfusion only yielded higher productivity strain of mushroomwith different colors without any changes in storage life.